Before I knew I loved you - Kawaguchi, Toshikazu, 1971- (Hanover Square Press, 2026)
"In a special seat in a fabled Tokyo cafe, you're offered something irresistible - not just a warm, comforting coffee, but the chance to go back in time to revisit the ones you love ... In Before I Knew I Loved You, Toshikazu Kawaguchi takes us back to the warm heart of the mysterious Funiculi Funicula Cafe, with another four guests whose luminous stories of love, lost and won again, will reaffirm your belief in its eternal potential."--Jacket flap.